2012
DOI: 10.1186/1477-7525-10-83
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the German version of the MacNew heart disease health-related quality of life questionnaire

Abstract: BackgroundThere is a lack of German-language, disease-specific health related quality of life instruments applicable in cardiac rehabilitation. The purpose of this project was to investigate the psychometric properties of the German version of the MacNew Heart Disease Health-related Quality of Life Questionnaire (MacNew) in patients undergoing cardiac rehabilitation.MethodsThe MacNew was filled out by 5692 inpatients. We analysed acceptance (number of missing values), ceiling and floor effects, reliability (Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 30 publications
(54 reference statements)
3
19
1
Order By: Relevance
“…The χ 2 /df ratio should be <2 in order to claim adequate fit and, in Model 1, the ratio was 1.39 indicating adequate fit. Although contrasting findings have been reported, for example in the English MacNew [ 25 ] and the German MacNew [ 27 ], the CFA in the current study suggested a 3-factor model for the MacNew. The interviewer-administered Sinhalese 3-factor MacNew is consistent with the original 3-factor structure of the self-administered MacNew [ 6 ] that has been substantially confirmed in each of the independently generated study reports in languages as diverse as Norwegian [ 11 ], Dutch [ 10 ], Chinese [ 28 ], Spanish [ 9 ] and Hungarian [ 29 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The χ 2 /df ratio should be <2 in order to claim adequate fit and, in Model 1, the ratio was 1.39 indicating adequate fit. Although contrasting findings have been reported, for example in the English MacNew [ 25 ] and the German MacNew [ 27 ], the CFA in the current study suggested a 3-factor model for the MacNew. The interviewer-administered Sinhalese 3-factor MacNew is consistent with the original 3-factor structure of the self-administered MacNew [ 6 ] that has been substantially confirmed in each of the independently generated study reports in languages as diverse as Norwegian [ 11 ], Dutch [ 10 ], Chinese [ 28 ], Spanish [ 9 ] and Hungarian [ 29 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The overall Cronbach's alpha is 0.96. This is comparable to its version in other languages, e.g., 0.94 for French version [10], 0.90 to 0.94 for Danish, Norwegian, and Swedish versions, respectively [11], 0.93 for Korean version [12], and 0.95% for German version [13]. But much higher than 0.80 of the Turkish version [14].…”
Section: Discussionsupporting
confidence: 50%
“…The emotional subscale, with one item, and the physical subscale, with 2 items, loaded most consistently with the original 3-factor structure. However, 5 of the social subscale items did not load with the original structure of the social scale which is consistent with similar proportions in other languages, e.g., German [14,30,31] and Portuguese [29]. The sexual activity item (#27) falls into the physical and social subscales in this report; however, this item was not included in the original factor analysis and has recently been shown to fall into the social rather than the physical subscale [22,29].…”
Section: Discussionsupporting
confidence: 79%